Prospects of utilization mining methane on the basis of gas hydrate technologies - Petlovanyi, Mykhailo; Sai, Kateryna; Prokopenko, Kostiantyn (My University, 2019)
The peculiarities of the innovative approach to the utilization of coal mine methane, which is extracted by significant volumes due to the technological process of underground development of coal-gas fields, are revealed. An innovative energy-saving technology for producing gas hydrates with the maximum possible accumulation of alternative gas volume on the basis of methane degassing systems of coal mines in the Western Donbass and transporting them to the infrastructure of the region to reduce the share of imported gas and pollution.
Keywords: gas hydrate, mine methane, coal mine, energy, degassing system